Growth of scale for juvenile coho salmon in the Bolshaya River (West Kamchatka) - Victor F. Bugaev; Nadezhda V. Yarosh (Известия ТИНРО, 2014)
Structure of scale is investigated for juvenile coho salmon. The samples were collected in the lower part of the Bolshaya River (West Kamchatka) in 2007-2012. The first scleritis bounding the central plate of scale is formed when body length of coho underyearlings achieves 38 mm, on average. In the investigated area, seasonal growth of scale starts and formation of next annuli of juvenile coho scale happens usually in the third 10-days of May: in the beginning of this period for one-year-old fish and in its end for two-years-old fish. The seasonal growth becomes slower again with water cooling in the last half of September, until its complete stagnation in October. Each scleritis forms in similar time, independently on age of juveniles: in 11.3 days for the underyearlings (data for in June-September), 10.1 days for one-year-old fish (data for June-September), and 11.2 days for two-years-old fish (data for in June-July). Additional zones of dense sclerites could form on the scale of juvenile coho within the growth season.